Analisis Resepsi Suku Non Bugis Terhadap Tradisi ‘uang panai’ dalam Film ‘uang panai’ Maha(r)l - Britania Widya Sista Hapsari Hapsari; Sumekar Tanjung (Program Studi Ilmu Komunikasi UII, 2022)
The Bugis tribe in South Sulawesi has a tradition that is still being carried out today, namely 'uang panai.' Uang Panai is given to the bride and groom. The purpose of this research is to examine the reception of Maha(r)l's film 'Uang Panai.' This study used qualitative research methods. Data was collected through in-depth interviews. The informants who were the subjects of the study were five people with the criteria of having watched the Maha(r)l film 'uang panai', a non-Bugis ethnic group living in Makassar. The results of the research show that by using Stuart Hall's reception analysis, the five informants' reception of Maha(r)l's ' Uang Panai' film is in a position of negotiation and opposition. None of the informants are in the hegemonic dominant model.